Copra agribusiness efficiency and institutional dynamics in Buton Regency, Indonesia: A structural equation modeling approach - Zarliani, Wa Ode Al; Wardana; Sukmawani, Reny; Mappasomba, Musadar (Asian Journal of Agriculture and Rural Development, 2026)
Coconuts are among Indonesia’s most important plantation commodities, yet copra farmers continue to face low bargaining power, weak institutions, and limited technology adoption. This study assesses the determinants of smallholder productivity and welfare in the copra value chain by integrating supply chain dynamics, market conditions, institutional capacity, and technology adoption. Research was conducted in Lawele Village, Buton Regency, using a mixed-methods design. Primary data were collected from 70 farmers and three collectors through surveys, interviews, and field observations. Analytical methods combined descriptive cost and flow analysis with Partial Least Squares Structural Equation Modeling (PLS-SEM). Results show that supply chain efficiency and market demand significantly influence farmer outcomes only when mediated by institutional strength and technology use. Institutions have the strongest effect on productivity and welfare, while technology adoption enhances quality and competitiveness when supported by stable demand and cooperative governance. These findings empirically support the Structure-Conduct-Performance (SCP) perspective by demonstrating that institutional arrangements and technology adoption function as critical transmission mechanisms between market structure and farmer welfare outcomes. This study also highlights the need for integrated policy interventions that prioritize institutional strengthening, cooperative-managed technology, and transparent market systems. The study suggests that policy implications, which are manifested through empowerment of rural cooperatives, facilitation of digital market access, and expansion of farmer training programs, are essential to enhance smallholder resilience.